2006
DOI: 10.1103/physrevlett.96.235503
|View full text |Cite
|
Sign up to set email alerts
|

Glasslike Two-Level Systems in Minimally Disordered Mixed Crystals

Abstract: THz spectroscopy is used to identify a broad distribution of two-level systems, characteristic of glasses, in the substitutional monatomic mixed crystal systems, Ba(1-x)Ca(x)F(2) and Pb(1-x)Ca(x)F(2). In these minimally disordered systems, two-level behavior, which was not previously known to occur, begins at a specific CaF(2) concentration. The concentration dependence, successfully modeled using the statistics of the impurity distribution in the lattice, points to a collective dopant tunneling mechanism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As a result, after a primary crystallization of a continuous series of Ba 1-x Ca x F 2 fluorite solid solutions with a minimum in the liquidus curve at x < 0.5, during the cooling there occurs a high-T (at 900 o C) solid-state decomposition into a two-phase mixture of dilute CaF 2 and BaF 2 -based solid solutions (Chernevskaya, & Anan'eva, 1966;Wrubel et al, 2006;Zhigarnovskii & Ippolitov, 1969). The phase diagram of this system has been recently reviewed by Fedorov et al (2005) who showed it does not contain a continuous solid solution.…”
Section: Mixed Alkali Earth Fluoride Systemsmentioning
confidence: 99%
“…As a result, after a primary crystallization of a continuous series of Ba 1-x Ca x F 2 fluorite solid solutions with a minimum in the liquidus curve at x < 0.5, during the cooling there occurs a high-T (at 900 o C) solid-state decomposition into a two-phase mixture of dilute CaF 2 and BaF 2 -based solid solutions (Chernevskaya, & Anan'eva, 1966;Wrubel et al, 2006;Zhigarnovskii & Ippolitov, 1969). The phase diagram of this system has been recently reviewed by Fedorov et al (2005) who showed it does not contain a continuous solid solution.…”
Section: Mixed Alkali Earth Fluoride Systemsmentioning
confidence: 99%
“…Amongst those, the behavior of the temperature dependence of the thermal conductivity ͑T͒ of glasses and disordered crystals continues to attract a significant research effort. 1 The most intriguing manifestation of the scattering of heat waves by either topological, 1 orientational, 2 chemical disorder, 3 defect crystals, 4 or even crystals with minimum disorder 5 concerns the quantitative similitude of ͑T͒ within a relatively wide range of temperatures ͑0.1-10 K͒, independent of the chemical composition. In stark contrast, most of our understanding of such phenomena relies on phenomenological constructs such as the two-level systems 1 ͑TLSs͒ or soft-potential 6 models ͑SPMs͒.…”
Section: Introductionmentioning
confidence: 99%